Inequality, material well-being, and subjective well-being: Exploring associations for children across 15 diverse countries. (February 2019) - Main, Gill; Montserrat, Carme; Andresen, Sabine; Bradshaw, Jonathan; Lee, Bong Joo
Abstract: Children's material well-being, and the levels of wealth and inequality in societies within which children live, are important factors in determining outcomes. However, less is known about the extent to which these factors have an impact children's subjective well-being, especially in an internationally comparative context. This study draws on data from the Children's Worlds survey, an international study of child subjective well-being, to explore links between national level indicators of wealth and inequality (GDP and Gini coefficients), individual indicators of material well-being (the material resources children report having access to), and subjective well-being. The survey covers 15 diverse countries covering the continents of Europe, Asia, Africa and South America, with samples of at least 3000 per country, ages 8, 10 and 12. Analysis takes the form of a multilevel, varying intercepts and slopes model, examining the association between financial and material resources and inequality and subjective well-being across and between countries. Findings suggest that material resources that children report are significantly associated with subjective well-being, while indicators of financial resources and inequality at the national level are not. While a significant association between material resources and subjective well-being is found across the whole sample, the magnitude of this association, and the association between school- and country-level material resources, varies markedly. Within different countries, the strongest material resources-related predictor of overall subjective well-being may be either at the individual, school or country level. Highlights: Children's Worlds survey data is useful in examining links between material living standards and subjective well-being. Across the 15 countries, significant associations exist between access to material resources and subjective well-being. Country-level measures of resources were not significantly associated with children's subjective well-being. Unequal access to resources at the school and country level were not significantly associated with subjective well-being. Material resources related to subjective well-being in all countries, but the type and magnitude of associations varied. Measuring material resource access in diverse international samples is complex and requires a great deal more research.